Learning from electricity markets: How to design a resilience strategy. (September 2022) - Fabra, Natalia; Motta, Massimo; Peitz, Martin
Abstract: Security of supply concerns are at the forefront of the public debate. The pandemic and post-pandemic times have demonstrated that preparing for global shocks requires the quick availability of some essential goods and services, including energy. Private incentives are typically insufficient for an economy to be prepared for rare events with large negative impacts. Instead, governments and preferably supranational institutions should implement mechanisms that make sure that prevention, detection and mitigation measures are taken. The economics of electricity capacity mechanisms provides valuable lessons for the provision of essential goods in such events, which need to be complemented with other elements aimed at mitigating the causes and impacts of potential crises. Highlights: Private incentives are insufficient to get prepared for rare events with negative impacts. Lack of a timely response and rationing make most market solutions socially unacceptable. Electricity capacity mechanisms illustrate the possibility to address security of supply concerns. A system of strategic reserves procured through auctions may perform well in most cases.